Functional analysis in clinical treatment - Sturmey, Peter (Practical resources for the mental health professional., 2020)
"This second edition of Functional Analysis in Clinical Treatment updates the material in keeping with DSM-5 and ICD-10 and provides 40% new information, including updated literature reviews, greater detail in the functional analysis/assessment sections of each chapter, two new chapters on autism spectrum disorders and chronic health problems, and examples of worked assessments, such as interview transcripts, ABC charts, and observational data."--Publisher's description